2011
DOI: 10.1111/j.1365-2095.2010.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary inclusion of peas, chickpeas and faba beans on growth, feed utilization and health of gilthead seabream (Sparus aurata)

Abstract: Three legumes [field peas (P), chickpeas (CP) and faba beans (B)] at two inclusion levels [170 g kg)1 (L) and 350 g kg)1 (H)] were evaluated in a 13-week experiment with triplicate groups of 92.6 +/- 5.0 g gilthead seabream (Sparus aurata L.). A control diet included wheat meal, fishmeal (FM) and a mixture of plant ingredients as protein sources. Diets were formulated to be isonitrogenous and isoenergetic and processed in a twin-screw extruder. Restricted feeding was applied (15 g kg)1 of body weight) and grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…The improvement in digestibility results from denaturation of protein, destruction of the trypsin inhibitor, or reduction of tannins and phytic acid (Liener, 1980;El-Adawy, 2002;Gaber, 2006). The extrusion process resulted in higher protein productive value of chickpea meal for gilthead bream Sparus aurata (Adamidou et al, 2011). In our study, heating during the extrusion process probably resulted in higher digestibility of chickpeas, as an ingredient.…”
Section: Discussionmentioning
confidence: 54%
“…The improvement in digestibility results from denaturation of protein, destruction of the trypsin inhibitor, or reduction of tannins and phytic acid (Liener, 1980;El-Adawy, 2002;Gaber, 2006). The extrusion process resulted in higher protein productive value of chickpea meal for gilthead bream Sparus aurata (Adamidou et al, 2011). In our study, heating during the extrusion process probably resulted in higher digestibility of chickpeas, as an ingredient.…”
Section: Discussionmentioning
confidence: 54%
“…Faba is primarily cultivated in the central and northern parts of Iran and is a common human food at different parts of the country. It contains 25-35 % crude protein, 50-60 % carbohydrate, 3-10 % lipid, and 16.2 kJ g -1 energy (Gaber 2006;Adamidou et al 2011). Raw faba beans also contain the alkaloids: vicine, isouramil, and covicine, which can induce hemolytic anemia in patients with a hereditary condition known as glucose-6-phosphate dehydrogenase deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the previous studies reported in fish nutrition have mainly focused on the possibility of partial or full replacements of fish meal diets with alternative plant protein sources (Kaushik et al 1995;Francis et al 2001). Among the plant sources such as beans, lupins, and peas (commonly known legumes), legumes are promising ingredients due to the relatively high protein and energy contents, and have been successfully assayed in different species of fish (Burel et al 2000;Farhangi and Carter 2001;Gaber 2006;Azaza et al 2009;Adamidou et al 2011;Bórquez et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, higher protein digestibility coefficients were obtained in comparison to those reported by Adamidou et al (2011) for Sparus aurata fed with diets prepared with chickpea (Cicer arietinum L.). They reported ADP of 80% for chickpea flour, while in the present investigation, using dehulled chickpea flour, resulted in ADP as high as 94.5 and 95.6%.…”
Section: Discussionmentioning
confidence: 46%
“…To overcome those limitations, processes need being implemented for, on one hand, improvement and utilization of large quantities of legumes and cereals stored for a long time (Drew et al, 2007;Adamidou et al, 2011;Valdez-González et al, 2013) and, on the other hand, reducing the content of fiber, tannins and increase protein digestibility by for, example, the elimination of the hull or dehulling . The objective of the present study was to test the effect of the processes of fermentation, hardening and dehulling on the chemical composition of chickpea (Cicer arietinum) grains, in vivo digestibility of ingredients, and antinutrients (phytic acid and tannins) in diets for Nile tilapia Oreochromis niloticus including flours of processed and non-processed grain chickpea.…”
Section: Introductionmentioning
confidence: 99%